IoT enable relay network for demand based light intensity controlled seamless highway lighting system - Rahman, Md. Arafatur; Yan Syafri, Hidayat; Muhammad, Kamil; M. Nomani, Kabir; A. Taufiq, Asyhari; Azad, Saiful (2018)
Highway authority spends huge amount of money per year for Highway Lighting System worldwide (e.g., Malaysia USD 25 Million per year). Internet of Things (IoT) becomes one of the popular concepts that provides prominent solutions in various paradigms. Exploiting IoT, this work develops a prototype for efficient highway lighting system at lower energy consumption. Two key features need to be taken into account for designing such a system are: i) Road users’ point of view (i.e., Comfort and safety) ii) Road service providers’ point of view (i.e., Reduce Energy Consumption and Maintenance Cost). The characteristics of this prototype revile the effectiveness of the proposal.